2019
DOI: 10.1111/sum.12511
|View full text |Cite
|
Sign up to set email alerts
|

Variations of SOC and MBC observed in an incubated brown loam soil managed under different tillage systems for 12 years

Abstract: To assess changes in organic carbon pools, an incubation experiment was conducted under different temperatures and field moisture capacity (FMC) on a brown loam soil from three tillage practices used for 12 years: no‐till (NT), subsoiling (ST) and conventional tillage (CT). Total microbial respiration was measured for incubated soil with and without the input of straw. Results indicated that soil organic carbon (SOC) and microbial biomass carbon (MBC) under ST, NT and CT was higher in soil with straw input tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…A variety of conservation farming practices can increase SOC levels, while also increasing crop productivity and decreasing water demand (Kumar et al, 2019;Mehra et al, 2018). Crop residue return to surface soils can have a positive effect on soil carbon sequestration (Chowdhury et al, 2015;Li et al, 2019b). For example, chopping and returning wheat straw and corn stover can increase SOC levels by 14.5% in a double-cropping system (Zhao et al, 2019).…”
Section: Soil Organic Carbonmentioning
confidence: 99%
“…A variety of conservation farming practices can increase SOC levels, while also increasing crop productivity and decreasing water demand (Kumar et al, 2019;Mehra et al, 2018). Crop residue return to surface soils can have a positive effect on soil carbon sequestration (Chowdhury et al, 2015;Li et al, 2019b). For example, chopping and returning wheat straw and corn stover can increase SOC levels by 14.5% in a double-cropping system (Zhao et al, 2019).…”
Section: Soil Organic Carbonmentioning
confidence: 99%
“…The benefit of conservation tillage on SOC accumulation was demonstrated, and the increase in SOC generally occurred in the top soil layer [42,43]. The results of this study indicated that the introduction of deep tillage into the C-RT could affect the availability of soil nutrients by changing the distribution of straw in soil, and increasing SOC in deep soil layers (Table 5).…”
Section: Changes In Soil Physical Properties With Different Tillage P...mentioning
confidence: 67%